Castleman Disease with MDM2/CDK4 Protein Expression: a Potential Mimic of Inflammatory Variant of Liposarcoma with Significant Consequences. (October 2022) - Georgantzoglou, Natalia; Baker, Michael; Liu, Xiaoying; Kerr, Darcy A.; Linos, Konstantinos
Castleman disease is a rare benign lymphoproliferative disorder that includes a spectrum of distinct histopathological entities. The differential diagnosis of Castleman disease is broad and includes lymphomas, HIV-related lymphadenopathy, autoimmune disorders, and inflammatory liposarcoma. When Castleman disease occurs in the retroperitoneum, the distinction from the inflammatory variant of well-differentiated liposarcoma can be very challenging in small biopsies. Herein we report a case of Castleman disease that presented as a retroperitoneal mass and expressed MDM2 and CDK4 by immunohistochemistry. To our knowledge, this is the first report of Castleman disease staining positively for MDM2/CDK4, and it underscores how immunohistochemistry can potentially serve as a pitfall when differentiating this rare entity from retroperitoneal sarcomas.